2011
DOI: 10.1182/blood-2010-09-299719
|View full text |Cite
|
Sign up to set email alerts
|

Platelet microRNA-mRNA coexpression profiles correlate with platelet reactivity

Abstract: MicroRNAs (miRNAs) regulate cell physiology by altering protein expression, but the biology of platelet miRNAs is largely unexplored. We tested whether platelet miRNA levels were associated with platelet reactivity by genome-wide profiling using platelet RNA from 19 healthy subjects. We found that human platelets express 284 miRNAs. Unsupervised hierarchical clustering of miRNA profiles resulted in 2 groups of subjects that appeared to cluster by platelet aggregation phenotypes. Seventy-four miRNAs were differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
318
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(340 citation statements)
references
References 44 publications
(70 reference statements)
20
318
0
2
Order By: Relevance
“…A year later, the same group established a correlation between platelet microRNA-mRNA coexpression profiles with platelet reactivity [28]. Two years later, Edelstein et al [29] narrowed the gap by showing that (i) miR-376c levels were inversely correlated with PCTP mRNA levels, PC-TP protein levels and PAR4 reactivity, and that (ii) miR376c regulated expression of PC-TP in human megakaryocytes [29].…”
Section: A Role For Micrornas In Platelet Function?mentioning
confidence: 99%
“…A year later, the same group established a correlation between platelet microRNA-mRNA coexpression profiles with platelet reactivity [28]. Two years later, Edelstein et al [29] narrowed the gap by showing that (i) miR-376c levels were inversely correlated with PCTP mRNA levels, PC-TP protein levels and PAR4 reactivity, and that (ii) miR376c regulated expression of PC-TP in human megakaryocytes [29].…”
Section: A Role For Micrornas In Platelet Function?mentioning
confidence: 99%
“…44 Alternatively, the increased number of BM-derived EC that line the microvascular network of the kidney of the LV-126 mice could serve as a source of miR-126 via the production of microparticles 45 ; it was recently shown that, under certain conditions, such particles can cross the tubular basement membrane. 46 In addition, activated platelets may be involved because miR-126 is among the most abundant microRNAs in platelets, 47,48 and they could serve as a transporter of miR-126 to the site of injury. 49 Because EPCs can take up platelets and their molecular content, 50 platelets could also add to EPC function through miR-126 transfer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the main question about platelet miRNAs concerns their possible role in regulating platelet reactivity. It has been reported that platelets contain more mRNAs that encode proteins that inhibit platelet activation to maintain platelets in a resting state [47]. Regarding activation, platelets miRNAs may be differentially expressed, thus some of them may predict platelet activation/reactivity [47].…”
Section: Beyond Aggregation: New Insight In Platelet Physiology and Fmentioning
confidence: 99%
“…It has been reported that platelets contain more mRNAs that encode proteins that inhibit platelet activation to maintain platelets in a resting state [47]. Regarding activation, platelets miRNAs may be differentially expressed, thus some of them may predict platelet activation/reactivity [47]. In light of the published data, we have tried to elucidate the molecular changes induced in activated platelets, looking at miRNome and proteome reorganization upon activation [46].…”
Section: Beyond Aggregation: New Insight In Platelet Physiology and Fmentioning
confidence: 99%